Efectos económicos, financieros y sociales causados por las variaciones en los precios del petróleo en Colombia (2017)
The document aims to show the impacts caused by the fall in oil prices in the last oil crisis in Colombia, starting from mid-2014 to date, addressing three sectors in particular, economic, financial and social. Initially, the economic impacts are exposed, reflecting the decrease in GDP, in tax revenues for the nation, in foreign investment and in exports; situations in which great affectations are seen for the national economy.